Frequency of Maternal and Fetal Complication in Obese Pregnant Women (Medical Forum Monthly, 2023)
Objective: To determine the frequency of maternal & fetal complication in obese pregnant women.Study Design: Descriptive case series studyPlace and Duration of Study: This study was conducted at the department of Obstetrics & Gynecology, Nishtar Medical University, Multan, from May 2021 to October 2021.aterials and Methods: A total of 264 pregnant females with BMI > 25kg/m2 were included in this research. These females were registered on predesigned proforma of all those women who booked themselves and were followed till delivery for maternal and fetal outcome, data was collected and analyzed.Results: The mean age of the women was 28.20±4.67 years. Frequency of maternal and fetal complications in obese pregnant women observed has been found high. Caesarean section rate 39.3% women, gestational hypertension 52.5%, gestational diabetes 18.9% and assisted birth 44.3%, macrosomia & still birth was 24.6% and 18.9% respectively.Conclusion: In a nutshell, outcomes of our study indicate that obesity caries significant increased risk for complications during pregnancy and delivery for both mother & fetus.